2023
DOI: 10.3390/nu15040965
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Choline Supplement in a Maternal Obesity Model Modulates Offspring Hepatic Lipidomes

Abstract: Maternal obesity during pregnancy adversely impacts offspring health, predisposing them to chronic metabolic diseases characterized by insulin resistance, dysregulated macronutrient metabolism, and lipid overload, such as metabolic-associated fatty liver disease (MAFLD). Choline is a semi-essential nutrient involved in lipid and one-carbon metabolism that is compromised during MAFLD progression. Here, we investigated under high-fat (HF) obesogenic feeding how maternal choline supplementation (CS) influenced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In addition, the male offspring demonstrated altered Ppara and Ldlr expression with the combined effect of prenatal and postnatal AE, while in female offspring, postnatal AE alone was sufficient to downregulate Ldlr expression. Overall, it seems that male offspring or those with a higher AE dosage were more susceptible to prenatal AE and responsive to CS [31,44,47]. In a prior study of 4 g/kg prenatal AE only, female offspring were found to have a greater reduction in SR-B1 and CYP7A1 cholesterol metabolic gene expression and thus potentially more susceptible to cholesterol dysregulation [9].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the male offspring demonstrated altered Ppara and Ldlr expression with the combined effect of prenatal and postnatal AE, while in female offspring, postnatal AE alone was sufficient to downregulate Ldlr expression. Overall, it seems that male offspring or those with a higher AE dosage were more susceptible to prenatal AE and responsive to CS [31,44,47]. In a prior study of 4 g/kg prenatal AE only, female offspring were found to have a greater reduction in SR-B1 and CYP7A1 cholesterol metabolic gene expression and thus potentially more susceptible to cholesterol dysregulation [9].…”
Section: Discussionmentioning
confidence: 95%
“…This fatty acid is exclusively catabolized in the peroxisome and its breakdown is considered a source for alkyl groups in plasmalogen synthesis [ 55 ]. Inversely, a supplementation of choline to pregnant mice fed with a high-fat diet increases the relative abundance of hepatic plasmalogen and sphingomyelin d42:2 (SM d18:1_24:1, containing nervonic acid) in fetus at 17.5 day of gestation and after 6 weeks postnatal in male offspring, indicating an antioxidative response to protect the mouse liver from damages due to high-fat feeding [ 56 ]. Another study has shown that choline supplementation increased the incorporation of DHA into choline-containing phospholipids in a mouse model of maternal obesity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from epidemiological, clinical, and animal studies have demonstrated that obesity affects not only maternal health, but also the long-term outcomes of offspring, with increased risk of obesity and cardiovascular disease (CVD) later in life [2][3][4]. Although the exact mechanisms of the transgenerational effect of maternal obesity remains unclear, fetal programming has been suggested to play a pivotal role in this process [5][6][7]. Human studies have provided evidence for the mechanisms underlying the link between maternal obesity and offspring cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%